Offshoring of R&D: Looking abroad to improve innovation performance - Nieto, María Jesús; Rodríguez, Alicia (Journal of International Business Studies, 2011)
The offshoring of knowledge services has become a phenomenon of increasing importance for firms, but many of its implications are yet to be discussed thoroughly. This paper analyzes whether R&D offshoring contributes to enhancing firms’ innovation capabilities. Specifically, the study distinguishes between two governance models of offshoring – captive offshoring and offshore outsourcing – and two types of innovation outcomes – product and process innovations. We suggest that R&D offshoring has different impacts, depending on the innovation results and governance models considered. The study empirically tests these relationships using the Spanish Technological Innovation Panel. This survey contains information on a large sample of firms from diverse sectors for the period 2004–2007. The empirical findings allow us confirm our hypotheses, and highlight the strategic importance of R&D offshoring. The empirical evidence reveals a positive relation between offshoring and innovation performance, with a greater effect on product than on process innovations. The results for different governance models show that captive offshoring has a greater effect on innovation outcomes than offshore outsourcing. These findings lead us to conclude that firms that look overseas can benefit from location-specific and specialization advantages to improve innovation performance.